Interaction effects of milling variables on energy consumption of stirred ball mill for chocolate refining - Fišteš Aleksandar; Rakić Dušan (Journal on Processing and Energy in Agriculture, 2015)
The aim of this study was to determine the effect of main milling variables on power requirements and energy consumption of laboratory ball mill refiner for chocolate. It is consisted of vertical cylinder, equipped with a rotating shaft with arms, and filled with steel balls as a grinding medium. Experiments were planned following a Box-Behnken design, considering the mass of the steel balls, retention time and agitator shaft speed as input factors. The power consumption (W) was recorded upon which milling energy consumption (J/kg) has been calculated. A second order polynomial model was fitted to the experimental data. A response surface regression analysis of both responses was performed. Significance of influence of the main parameters and their interactions are obtained by analysis of variance and residual analysis. It is shown that the power requirements are highly influenced by the agitator shaft speed with contribution >95 %. Retention time and agitator shaft speed are the milling variable with the most significant influence on energy consumption with contributions of 76 % and 12 %, respectively.